The relation between patient discomfort and uncompensated forces of a patient support device for breast and regional lymph node radiotherapy. (October 2018) - Boute, Bert; Veldeman, Liv; Speleers, Bruno; Van Greveling, Annick; Van Hoof, Tom; Van de Velde, Joris; Vercauteren, Tom; De Neve, Wilfried; Detand, Jan
Abstract: Although many authors stated that a user-centred design approach in medical device development has added values, the most common research approach within healthcare is evidence-based medicine, which tend to focus on functional data rather than patient wellbeing and comfort. End user comfort is well addressed in literature for commercial products such as seats and hand tools but no data was found for medical devices. A commercial patient support device for breast radiotherapy was analysed and a relation was found between discomfort and uncompensated internal body forces. Derived from CT-images, simplified patient free-body diagrams were analysed and pain and comfort evaluated. Subsequently, a new patient position was established and prototypes were developed. Patient comfort- and prototype optimization was done through iterative prototyping. With this approach, we were able to compensate all internal body forces and establish a force neutral patient free-body diagram. This resulted in comfortable patient positioning and favourable medical results. Graphical abstract: Image 1 Highlights: Comfort was analysed for a commercial breast radiotherapy patient support device. Patient position was studied through CT scans, surveys and free body diagrams. We found a relation between discomfort and uncompensated internal body forces. Device prototypes were developed, which achieved a force neutral patient position. The new support device has improved comfort, patient position and medical results.